2016
DOI: 10.1016/j.neurobiolaging.2016.03.025
|View full text |Cite
|
Sign up to set email alerts
|

NIA-AA staging of preclinical Alzheimer disease: discordance and concordance of CSF and imaging biomarkers

Abstract: The National Institute of Aging and Alzheimer’s Association (NIA-AA) criteria for Alzheimer disease (AD) treat neuroimaging and cerebrospinal fluid (CSF) markers of AD pathology as if they would be interchangeable. We tested this assumption in 212 cognitively normal participants who have both neuroimaging and CSF measures of β-amyloid (CSF Aβ1-42 and PET imaging with Pittsburgh Compound B) and neuronal injury (CSF t-tau and p-tau and structural MRI) with longitudinal clinical follow-up. Participants were class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 46 publications
(69 reference statements)
7
78
1
1
Order By: Relevance
“…Because of the low number of studies, results from this analysis are presented with caution. One study (Vos et al, 2016), presented data separately for amyloid determined via CSF and PET, so this study was considered as two separate studies for this analysis, yielding a total of 10 studies. Demographic data per dataset is presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the low number of studies, results from this analysis are presented with caution. One study (Vos et al, 2016), presented data separately for amyloid determined via CSF and PET, so this study was considered as two separate studies for this analysis, yielding a total of 10 studies. Demographic data per dataset is presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…19,35,48 This heterogeneity suggests that multiple pathways could lead to abnormal markers of neuronal injury and ND. Individuals who are initially classified as SNAP but go onto demonstrate Aβ + would technically then fall into preclinical stage 2.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to potential incongruences in markers of ND, 35 participants were classified into NIA-AA stages at baseline in 2 ways. For the first set of analyses, baseline ND+ was defined using only HCV z .…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with this hypothesis of heterogeneity of MCI A-N+ etiologies, we found that among all MCI A-N+, only 20% were positive by both biomarkers, whereas they were 47% in the MCI A+N+ (supplementary Table S4). However, it has been also proposed that MCI A-N+ may reflect a proportion of AD individuals with subthreshold Aß SUVr (Vos et al, 2016(Vos et al, , 2015. We SUVr in MCI A-N+ classified using CSF Aβ 42 as amyloid biomarker (Wisse et al, 2015).…”
Section: Patients Positive For Neurodegeneration Only (Mci Snap)mentioning
confidence: 94%